Prediksi Financial Distress Dengan Model Springate Dan Zmijewski: Studi Kasus PT Sepatu Bata, Tbk. - Evieana R Saputri (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2025)
This study aims to analyze the potential for financial distress at PT Sepatu Bata, Tbk. during the 2019–2023 period using the Springate and Zmijewski models. The background of this research lies in the intense competition within the footwear industry, the emergence of innovative products from new competitors, and the significant financial downturn caused by the COVID-19 pandemic. A quantitative descriptive approach was applied, utilizing secondary data from audited annual financial statements obtained from the Indonesia Stock Exchange (IDX). The Springate model combines four financial ratios to calculate the S-Score, while the Zmijewski model uses three key financial ratios to produce the X-Score. The findings indicate that the Springate method achieved 100% accuracy in predicting financial distress without any Type I or Type II errors. In contrast, the Zmijewski method achieved only 40% accuracy, with a Type II error rate of 60%, demonstrating its lower effectiveness in detecting companies experiencing financial difficulties. Based on these results, it is concluded that the Springate model is more reliable and effective in identifying financial distress compared to the Zmijewski model, as it incorporates a more comprehensive range of financial indicators, including liquidity, profitability, and activity ratios. This research provides important implications for companies and investors in identifying potential bankruptcy risks early and taking strategic measures to improve financial performance. Future research is recommended to use a broader range of predictive models and to extend the study period for more comprehensive and accurate results.